Peningkatkan Motivasi Guru Dalam Mengajar Melalui Metode Problem Solving di SDN 016 Tanah Merah Kabupaten Kampar - Suriady, Suriady (Komunitas Manajemen Kompetitif, 2017)
Teachers need motivation in teaching, teachers who have high motivation in teaching can be seen from the spirit in giving lessons to learners. This will affect the quality of educational outcomes received by learners. Various problems to build teacher motivation include the attention in paying attention to various problems faced by teachers in work. As principal, there needs to be an effort to pay attention to teacher issues. This research is a school action research by applying problem solving method and analyzed by qualitative technique. Based on the results of research known that the application of problem solving method can increase the motivation of teachers in teaching in school. Keywords: Teacher motivation, problem solving